1997
DOI: 10.1109/10.594896
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of impedance and inductance ventilation sensors on adults during breathing, motion, and simulated airway obstruction

Abstract: The goal of this study was to compare the relative performance of two noninvasive ventilation sensing technologies on adults during artifacts. We recorded changes in transthoracic impedance and cross-sectional area of the abdomen (abd) and rib cage (rc) using impedance pneumography (IP) and respiratory inductance plethysmography (RIP) on ten adult subjects during natural breathing, motion artifact, simulated airway obstruction, yawning, snoring, apnea, and coughing. We used a pneumotachometer to measure air fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 17 publications
0
60
0
Order By: Relevance
“…It has been demonstrated that for RIP, the sum of RC and AB outperforms individual use of RC or AB for breath detection [5]. Therefore, in our study, RC and AB displacements were linearly combined with unit coefficients to represent the respiratory movement during exercise [2].…”
Section: Methodsmentioning
confidence: 97%
“…It has been demonstrated that for RIP, the sum of RC and AB outperforms individual use of RC or AB for breath detection [5]. Therefore, in our study, RC and AB displacements were linearly combined with unit coefficients to represent the respiratory movement during exercise [2].…”
Section: Methodsmentioning
confidence: 97%
“…[ 47,48 ] These types of sensors can be highly accurate and can more easily detect certain conditions than chest-based sensors, such as respiratory obstructions in which air stops fl owing into the lungs despite continued motion of the chest. [ 45,49 ] Strain sensors on the torso also tend to respond to other body motions in addition to respiration, such as walking, speaking, and arm movement, [ 43,49,50 ] whereas sensors on the nose and throat are not susceptible to such motion artifacts. However, sensors on the nose and throat are likely to be more conspicuous and less comfortable than those on the torso.…”
Section: Reviewmentioning
confidence: 98%
“…In contrast, impedance measures changes in electrical resistance, which usually are not linearly related to changes in cross-sectional dimensions. [12][13][14] Consistent with evidence-based guidelines on sensor evaluation, we evaluated the comparability of respiratory event and effort detection when using PVDF impedance belts (PVDFb) compared to currently recommended sensors, including RIP, NPT, heat-sensitive thermistry, and nasal-oral pneumotachography (PNT).…”
Section: Quantitative Measurements: Reference Standardmentioning
confidence: 99%